2002
DOI: 10.1104/pp.007179
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Rice Dwarf Mutant with a Defect in Brassinosteroid Biosynthesis

Abstract: We have isolated a new recessive dwarf mutant of rice (Oryza sativa L. cv Nipponbare). Under normal growth conditions, the mutant has very short leaf sheaths; has short, curled, and frizzled leaf blades; has few tillers; and is sterile. Longitudinal sections of the leaf sheaths revealed that the cell length along the longitudinal axis is reduced, which explains the short leaf sheaths. Transverse sections of the leaf blades revealed enlargement of the motor cells along the dorsal-ventral axis, which explains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(186 citation statements)
references
References 49 publications
5
173
1
1
Order By: Relevance
“…In addition, increased adaxial cell division, but not cell elongation, in the collar of lc2 further showed that LC2 serves as a negative regulator of cell division at the lamina joint to regulate leaf inclination. Although the numbers of leaf bulliform cells were increased under LC2 deficiency, we propose that this mainly contributes to the leaf rolling phenotype (motor cells have an important role in leaf rolling [1,44]), and the resultant changed physical shape and altered tissue flexibility might not lead to the bending of leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increased adaxial cell division, but not cell elongation, in the collar of lc2 further showed that LC2 serves as a negative regulator of cell division at the lamina joint to regulate leaf inclination. Although the numbers of leaf bulliform cells were increased under LC2 deficiency, we propose that this mainly contributes to the leaf rolling phenotype (motor cells have an important role in leaf rolling [1,44]), and the resultant changed physical shape and altered tissue flexibility might not lead to the bending of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analyses were carried out on the Rotor-Gene real-time thermocycler R3000 (Corbett Research) with Real-Time PCR Master Mix (Toyobo). The primers used were as follows: LC2 (5′-AGC ATC AGC TTT GGA CGA GGA-3′ and 5′-CAG TTG GTG GAA TAG AGC CAG AAT-3′), R2 (5′-TCT GCA CCT CCA CTT CGC TCA-3′ and 5′-TAG GTG GTG GCC TTG GAA GCT-3′), H3 (5′-AGC GAA GAG GAG ATG GCC CGT-3′ and 5′-AGG AGC TCC GTG CTC TTC TGG T-3′), CDKA;1 (5′-ATC ACG GCA ACA TCG TCA GG-3′ and 5′-AGT AAG CAA CGC CGC GGA GTA-3′), CDKA;2 (5′-ACC ACC GCA TAG TCA AAT CGT T-3′ and 5′-ACC ACA ATG TCA CCA CCT CGT GA-3′), XTR1 (5′-AGC CGT ACA TCC TGC AGA CGA-3′ and 5′-GCC CAG GTC CTT GCT GTT CT-3′), CPD1 (5′-TCT TCT CCA TCC CCT TTC CTC T-3′ and 5′-TCA AGA AGC TCC TCA ACC ATG T-3′ [44]), DWF4 (5′-AGT CGC GTG CTG CCA TTC T-3′ and 5′-AGC TCA GCA AGA GGT CCA GGA T-3′ [3]), BRI1 (5′-TAC CAG AGC TTC AGA TGC ACC A-3′ and 5′-AGT AGC TCA GGG TCG AAG ACA T-3′ [13]), OsGA2ox3 (5′-TTC TTC GTC AAC GTC GGC GAC TCG TTG C-3′ and 5′-TCT CAA ACT GGG CCA GCC TGT TGT CTC C-3′ [39]), OsGA20ox2 (5′-TAC TAC AGG GAG TTC TTC GCG GAC AGC A-3′ and 5′-TGT GCA GGC AGC TCT TAT ACC TCC CGT T-3′ [39]), OsIAA1 (5′-GCC GCT CAA TGA GGC ATT-3′ and 5′-GCT TCC ACT TTC TTT CAA TCC AA-3′ [40]), OsIAA9 (5′-AAG AAA ATG GCC AAT GAT GAT CA-3′ and 5′-CCC ATC ACC ATC CTC GTA GGT-3′ [40]), and OsIAA24 (5′-GGC TTG TGC TCT TCG TTG CT-3′ and 5′-CCT CTT GGA TTC AGA AAC ACT GAA-3′ [40]). …”
Section: Qrt-pcr Analysismentioning
confidence: 99%
“…In addition, BR regulates multiple developmental and physiological processes, such as vascular differentiation, reproductive development, photomorphogenesis, and stress responses (Clouse and Sasse, 1998;Bishop and Koncz, 2002;Fukuda, 2004). BR-deficient and BR-insensitive mutant plants show dwarfism, dark-green leaves, male sterility, and constitutive photomorphogenesis in the dark (Chory et al, 1991;Szekeres et al, 1996;Li and Chory, 1997;Mori et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The role of BRs in vascular development was supported by phenotypes of BR signaling mutants in Arabidopsis, rice, and Zinnia (Cano-Delgado et al, 2010; Mori et al, 2002). The BR deficient mutant, constitutive photomorphogenic dwarf (cpd) was first identified to be defective in BR biosynthesis and has exhibited severe decline in xylem biogenesis (Szekeres et al, 1996).…”
Section: Brassinosteriods Gibberellin and Ethylenementioning
confidence: 99%